Electoral Punishment and Protest Politics in Times of Crisis - Björn Bremer; Swen Hutter; Hanspeter Kriesi (Contention in Times of Crisis. Recession and Political Protest in Thirty European Countries, 2020)
This chapter links the political consequences of the Great Recession on protest and electoral politics. The economic voting literature offers important insights on how and under what conditions economic crises play out in the short run. However, it tends to ignore the closely connected dynamics of opposition in the electoral and protest arena. Therefore, this chapter combines the literature on economic voting with social movement research. It argues that economic protests act as a `signalling mechanism' by attributing blame to decision-makers and by highlighting the political dimension of deteriorating economic conditions. Ultimately, massive protest mobilization should thus amplify the impact of economic hardship on electoral punishment. The empirical analysis to study this relationship combines the data on protest with a dataset of electoral outcomes in thirty European countries from 2000 to 2015. The results indicate that the dynamics of economic protests and electoral punishment are closely related and that protests contributed to the destabilisation of European party systems during the Great Recession.
Keywords: 300; protest politics; economic crisis; electoral politics; economic voting; mainstream parties; party systems; political left